Dampak Kontrak Psikologis dan Motivasi Kerja Guru - Luluh Abdilah Kurniawan (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
This article aims to obtain information about the influence of psychological contract and organizational commitment to teacher work motivation in private SMK Kecamatan Pondok Gede, Bekasi. This research uses survey method with path analysis. The results showed there was a direct positive influence of psychological contract and organizational commitment to work motivation, with correlation coefficient value of 0.390 and coefficient value of 0.281.